Strategi Penyelesaian Konflik Tenurial Melalui Kemitraan Konservasi Di Taman Nasional Bunaken (Studi Kasus Pulau Mantehage) - Pandu Wijaya; Hengki Djemie Walangitan; Wieske Chriesti Rotinsulu (Sam Ratulangi University, 2022)
This research aims to analyze stakeholders for the implementation of conservation partnerships on Mantehage Island and formulate strategies for implementing conservation partnerships on Mantehage Island. This research was conducted from April to July 2022. The research method used a qualitative and quantitative descriptive approach. Primary data were obtained through direct interviews with managers of the Bunaken National Park area, village governments and community leaders on Mantehage Island. The questionnaire was conducted on the people on Mantehage Island with a total of 30 respondents who have plantation land on Mantehage Island. Secondary data was obtained from the Bunaken National Park Management Plan document for 2019-2028 as well as village monograph data. The results showed that there were seven stakeholders with the implementation of conservation partnerships on Mantehage Island, namely the Bunaken National Park Office, Local Communities, Village Governments and Non-Governmental Organizations as Key Players; Farmer's Group is located as Subject; Academics/Universities are located as Context Setters and Investors are located as Crowd. The results of the analysis related to the strategy of implementing conservation partnerships on Mantehage Island using the SWOT method show a position in quadrant I, namely supporting an aggressive strategy in which the implementation of conservation partnerships on Mantehage Island is supported by great strengths and opportunities.